Risk factors associated with postpartum haemorrhage at Juba Teaching Hospital, South Sudan, 2011 - Thomas Tako Akim Ujjiga; Jared. O. Omolo; Mathias OAketch; Erneo Benardo Ochi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
Objective: To study risk factors associated with post partum haemorrhage (PPH) in Juba Teaching Hospital, South Sudan. Method: An unmatched case control study was conducted in which 44 cases and 88 Controls were involved, from September to December 2011. Data was collected using a structured questionnaire in face to face interviews, and analyzed using Epi-info 3.5.3 statistical programme to determine if there was a correlation. Results: Maternal demographic and obstetric characteristics were found to be associated with the risk of bleeding during Bivariate analysis. However, age was found to confound emergency admission, uterotonic use (Oxytocin and Misoprostol) use and delivery type, the latter being modified, in the development of post partum haemorrhage. Conclusion: These results indicate that active management of the third stage of labour (AMTSL) and prompt intervention reduced the risk of developing PPH. Understanding the factors that cause PPH will allow us to better strengthen and effect pre delivery and emergency obstetric care which may help us reduce maternal mortality due to post partum haemorrhage.